2023
DOI: 10.1039/d3fo00797a
|View full text |Cite
|
Sign up to set email alerts
|

Goat and cow milk differ in altering the microbiota composition and neurotransmitter levels in insomnia mouse models

Abstract: Milk can improve sleep, and the effect of different animal milk vary. Accordingly, we evaluated the effectiveness of goat milk and cow milk in alleviating insomnia. The findings demonstrated that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Meanwhile, compared with the model group, the YPVEPF treatment at a high dose significantly increased the 5-HT and DA contents with a dose-dependent relationship. It has been proved that goat and cow milk could improve the neurotransmitter levels in insomnia mouse models . Some research indicated that the content of neurotransmitters in serum could predict their concentration in brain. , Hence, YPVEPF had the potential to recover the neurotransmitter system to improve sleep and anxiety in a peripheral circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, compared with the model group, the YPVEPF treatment at a high dose significantly increased the 5-HT and DA contents with a dose-dependent relationship. It has been proved that goat and cow milk could improve the neurotransmitter levels in insomnia mouse models . Some research indicated that the content of neurotransmitters in serum could predict their concentration in brain. , Hence, YPVEPF had the potential to recover the neurotransmitter system to improve sleep and anxiety in a peripheral circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic exposure to stress, such as unhealthy diet, inadequate exercise, and overuse of electronics, would damage the brain and body function, which is linked to a variety of neurodegenerative and mental disorders . According to epidemiological surveys, 27% of people suffer from sleep disorders in the world . Therefore, chronic-stress-induced anxiety, insomnia behaviors, and brain dysfunction have raised increasing concern.…”
Section: Introductionmentioning
confidence: 99%